Implementasi Algoritma FIFO Pada Aplikasi Pemesanan Menu Makanan dan Minuman Berbasis Android - Tegar Nuzululrahmat; Tri Widodo; Saucha Diwandari (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The culinary sector is a sector whose growth is quite promising, for example Mie Gacoan with the tagline "master of noodles". Mie Gacoan is a food restaurant from Indonesia. This business was founded in early 2016 in Malang and is a subsidiary of PT Pesta Pora Abadi. In 2021, Mie Gacoan has 54 stores in Indonesia with the majority of branches in East Java and Central Java. Mie Gacoan has become one of the destinations for college students and the local community to enjoy spicy noodles. Due to the large number of Mie Gacoan visitors, it is not uncommon for other visitors to have to be willing to queue for a long time to be able to enjoy the spicy noodles at Mie Gacoan. Therefore, the use of technology applied in restaurants is to reduce queues and apart from that, the application that will be created will provide information about food and drinks at Mie Gacoan. This application is designed based on Android using the Firebase database, and uses the Waterfall approach method. The results of testing this application using the System Usability Scale (SUS) method obtained an average score of 80.17. With these results, Mie Gacoan customers feel that this application can help Mie Gacoan customers a little to make it easier to order